Wide stability in a new family of optimal fourth‐order iterative methods. Issue 2 (3rd April 2019) - Chicharro, Francisco I.; Cordero, Alicia; Garrido, Neus; Torregrosa, Juan R.
Abstract : A new family of two‐steps fourth‐order iterative methods for solving nonlinear equations is introduced based on the weight functions procedure. This family is optimal in the sense of Kung‐Traub conjecture and it is extended to design a class of iterative schemes with four step and seventh order of convergence. We are interested in analyzing the dynamical behavior of different elements of the fourth‐order class. This analysis gives us important information about the stability of these members of the family. The methods are also tested with nonlinear functions and compared with other known schemes. The results show the good features of the introduced class.